Rural school turnaround and reform : it's hard work! - Meyers, Coby V.; Darwin, Marlene (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"We have entitled the fourth book in the series Rural School Turnaround and Reform: It's Hard Work! Overall, the body of scholarly work and research that examines school turnaround and reform in rural areas is slim; as such, this volume can add to the body of work and contribute to new knowledge in a much-needed area. In this volume, we seek chapter contributions that will speak to the challenges, successes, and opportunities to improve low-performing rural schools. Chapters range from conceptual arguments to policy analyses or research findings, as well as some combination of these or other ways to consider the work"-- Provided by publisher.
Keywords: Education, Rural -- Planning.; School improvement programs.; Educational change.; Rural schools -- Administration.; Education -- Rural.; Educational strategies and policy.; Education.; Rural communities.; elektronické knihy; electronic books